Nucleic Acid based detection of salmonellae in poultry - Muthuramalingam M (Department of Veterinary Microbiology, College of Veterinary and Animal Science, 2005)
In the present study detection of salmonellae by Polymerase Chain Reaction in avian bio-materials was carried out. Isolation of salmonellae from avian bio-materials was also done. Differentiation of salmonellae based on molecular methods was carried out. Thirteen isolates from chicken and two from quails were characterized as Salmonella gallinarum using standard bacteriological procedures. With regard to the fermentation of the sugars all isolates fermented dulcitol, maltose, arabinose, trehalose, and mannitol. Variation in fermentation pattern was observed with xylose and sorbitol. All isolates were uniformly sensitive to chloramphenicol, ciprofloxacin, enrofloxacin, and pefloxacin, while all were resistant to tetracycline, furazolidone and cloxacillin. Two isolates were serotyped as Salmonella gallinarum by the National Salmonella and Escherichia Center, Kasauli. Forty-six samples were positive by both genus specific as well as serovar specific PCR. The genus specific and serovar specific PCR were used to confirm the identity of the isolates. Performing PCR on template DNA prepared from RV broth enriched sample was found to be an extremely rapid method for detection of Salmonella. Restriction enzyme analysis of the amplicon from the rfbS gene with enzyme Tfi І of all isolates revealed the expected 235 bp digestion. All the isolates carried plasmids. Two plasmid profiles were observed among the isolates examined. A multiplex PCR for virulence plasmid was carried out. The expected 571 bp level amplification, which is specific for Spv virulence region and 284 bp level amplification, which is specific for genus Salmonella, were obtained in all the isolates. An allele-specific PCR method was developed for serotype-specific detection of S. gallinarum. The expected 187 bp level amplicons were obtained in all the isolates. The sequence of the rfbS gene product has been submitted to the Genbank and has been assigned the accession No AF 442573 ATCC 9184 . The sequence showed 99 per cent identity with Salmonella gallinarum.